The Poetic Prophecy of Marco Aguilar - Vargas Acuña, Gabriel (2024)
In this article, literary critic Gabriel Vargas follows the historical sequence of each of Marco Aguilar’s six collections of poems, to better understand the origin and evolution of his poetic technique, as well as to unveil his main motivations and existential concerns as a writer.